Edukimia Vol 4 No 1 - Februari 2022 - Editorial - Front Cover, TOC, Editorial - Tim Editorial Edukimia (Universitas Negeri Padang, 2022)
Edukimia - Vol. 04, No. 01 (February 2022) - Front Cover, Contents, and Editorial